Development of force plate for prosthetic applications interfacing with internet of things - Bharat Satya Kumar, Y; Kalyan Chakravarthy, Y; Prasad Paladagu, Ratna; Venkatesh, R; Srinath, A (International Journal of Engineering and Technology, 2018)
Force Plate is a measuring instrument which is used to calibrate the ground reaction force in gait cycle analysis of a subject (human or animal). Force plates are used to examine the lower limb kinematics for the applications of prosthetics, sports etc. In this study, a prototype of force plate is developed indigenously in an economical manner. It comprises of two metallic frames with a load cell (force transducer) mounted between them to produce an electrical signal as output, that is proportional to the amount of force applied on the surface of force plate. This prototype has a maximum load capacity of 3000N. The design of the force plate system along with the ground reaction force analysis and results are discussed below. Â Â